Dose-dependent response to infection with SARS-CoV-2 in the ferret model and evidence of protective immunity - Kathryn A. Ryan (Nature Portfolio, 2021)
SARS-CoV-2 induces mild infection in ferret model. Here, Ryan et al. characterise optimal infection dosage inducing upper respiratory tract (UTR) viral shedding, progression time of viral shedding, and pathology in ferrets and finally provide evidence for protection after re-challenge.